PERSEPSI ORANG TUA TENTANG KEMANDIRIAN MAKAN ANAK USIA 3-4 TAHUN - Itsna Faraniesya; Hapidin Hapidin; Hikmah Hikmah (Al Hanin, 2022)
Research aims to obtain empirical data about parents' perception of 3-to-4-year-old self-feeding children in Tebet Subdistrict, South Jakarta. The sample of this research was parents who have a 3-to-4-year-old child in Tebet Subdistrict, South Jakarta. Cluster random sampling was implemented. The method used in this research was quantitative by surveying. The data analytics technique used was descriptive statistics. The overall result of this research shows that parents' perception of 3-to-4-year-old self-feeding children in Tebet Subdistrict, South Jakarta categorized as good enough. By calculating data obtained from 45 parents shows that 44% of the parents were categorized as good enough. Then, 40% of the parents were categorized as deficient, and 16% remain was categorized as good. The results of this research depicted that parents were quite good in explaining the meaning of self-feeding children aged 3 to 4 years, quite good in understanding the importance of self-feeding children aged 3 to 4 years, quite good in understanding the meaning of self-feeding children aged 3 to 4 years, quite good in interpreting the aspects of self-feeding children aged 3 to 4 years, and quite good in behaving towards self-feeding children aged 3 to 4 years. The results of this research are expected to be used to help parents reaching self-feeding children aged 3 to 4 years so the self-feeding in children could be developed properly.Â Keywords: Parents' perception, Children's eating independence, Children aged 3-4 years